Deformation of acetabular press-fit cups: Influence of design and surgical factors. (October 2019) - Messer-Hannemann, Philipp; Campbell, Graeme M.; Morlock, Michael M.
Abstract: Background: Deformation of acetabular cups when press-fitted into an undersized cavity is inevitable due to the inhomogeneous stiffness of acetabular bone. Thinner cups or screw holes might increase the risk of high cup deformation. The aim of this study was to examine the influence of cup design and liner assembly on the deformation response during cup implantation. Methods: Acetabular cups with different designs were implanted into polyurethane foam models simulating the anatomical situation with nominal press-fits of 1mm and without nominal press-fits (line-to-line). Deformations were determined using a tactile coordinate measuring machine. A 3D laser scanner was used to determine the contact conditions at the cup-cavity interface. Polyethylene and ceramic liners were assembled to the implanted cups and the influence of the insertion on the deformation response evaluated. Fixation strength of the cups was determined by push-out testing. Findings: Cup deformation increased with smaller wall thickness ( P < 0.037) and screw holes ( P < 0.001). Insertion of ceramic liners reduced the deformation ( P < 0.001), whereas polyethylene liners adapted to the deformation of the implanted cups ( P > 0.999). Thin-walled cups exhibited a higher fixation strength for similar implantation forces ( P = 0.011). Interpretation: Thin-walled cups achieved higher fixation strengths and might be more bone-preserving. However, in combination with screw holes and high press-fit levels, wall thickness should be considered carefully to avoid excessive cup deformations leading to potential complications during liner assembly. Line-to-line insertion of thin-walled cups should be accompanied with a rough surface coating to minimize the loss of fixation strength due to the low press-fit fixation. Highlights: Reduced cup wall thickness and screw holes increased cup deformation. Thin-walled cups achieved higher fixation due to increased cup deformation. Polyethylene liner adapted to the cup deformation after assembly. Insertion of ceramic liner reduced the cup deformation.